Dividend Policy, Financial Leverage and Ownership Structure: Empirical Evidence from Vietnam - Nguyen, Do Quyen; Tran, Thi Minh Tram (Journal of International Economics and Management, 2016)
We examine the impact of leverage and state and foreign ownership structure on dividend payout policy of non-financial listed firms on both Ho Chi Minh and Hanoi Stock Exchange of Vietnam from 2010-2015. Our results suggest that firm with high level of debt tend to pay less dividend due to their financial constrain. Moreover, dividends are used as a signal of good performance to investors. Thus, firms tend to keep stable dividend policy over time. In addition, firms with higher portion of shares owned by the government are more likely to pay out more dividends. Meanwhile, foreign investors are found to have power in monitoring managers so they do not have to use dividend policy as the tool to reduce the free cash flow problem